Self-harm in the very old one year later: has anything changed?. (27th June 2019) - Wand, Anne Pamela Frances; Draper, Brian; Brodaty, Henry; Peisah, Carmelle
Abstract: Objectives: To follow-up a cohort of older people who self-harmed, their carer, and general practitioner (GP) and examine their reflections on the self-harm, care experiences, and outcomes. Design: Qualitative in-depth interviews. Setting: Two teaching hospitals and associated community services. Participants: Twelve-month follow-up of participants aged 80 or older who self-harmed, their nominated carers, and GPs. Measurements: A geriatric psychiatrist gathered data through patient and carer interviews using a narrative inquiry approach and from medical records. Interviews were audio recorded and transcribed. N-VIVO facilitated data organization for thematic analysis. Questionnaires sent to the patient's GP examined their perspectives and aspects of care relating to the self-harm. Results: Nineteen patients (63% baseline sample), 29 carers (90.6%), and 11 GPs (36.7%) were available at follow-up. Themes emerging from patients were "denial and secrets;" "endless suffering;" "more invalidation;" "being heard;" and "miserable in care." Themes from carer interviews were "denial and secrets;" "patient's persistent wish to die;" "abandonment by clinicians;" "unending burden for the carer;" and "distress regarding placement." General practitioner themes were "the problem is fixed;" "the troops have arrived;" and "I understand." Conclusions: Factors contributing to self-harm persisted at follow-up. Positive and negative responses were identified in the older person's system, highlighting areas for potential intervention. A conceptual framework for understanding self-harm in the very old was derived that emphasized the importance of understanding individual needs, the interpersonal context of the older person, and carer burden. Interventions should improve communication, facilitate shared understanding of perspectives, and provide support at all levels.